ARATICUM ACCESSIONS: EFFECT OF GIBBERELLIC ACID CONCENTRATIONS AND SOAKING TIMES ON SEED DORMANCY OVERCOMING - Silva, Edvan Costa da (2021)
The germination process of the Annona sylvatica A.St.-Hil becomes difficult because the seeds have physical and physiological numbness. Although, the objective was to evaluate the effect the gibberellic acid can have in overcoming this physiological process. So that, aimed to evaluate the effect of the gibberellic acid in the overcoming dormancy of araticum seeds. Two different projects were developed simultaneously (plants germination in the laboratory and emergence of seedlings in seed). At the laboratory, the experimental design used was completely casualized in factorial scheme 4 x 4. Evaluating the physiological aspect of the germination and vigor. The germination of the seeds presented superior performance when they were immersed in 1200 mg.L-1 of GA3, in 24 h of imbibition, reaching 67% of germination. In the emergence of seedlings in seed, the experimental design used was to randomize blocks in factorial scheme 4 x 5 (four accesses x five periods of immersion). After 110 days, evaluating physiological aspects of emergence and vigor. The emergence varied between 32 to 45% (accesses A1 and A3) in a period of 15 to 24 h (accesses A1 and A3 or A4). High concentration and longer period of soaking in gibberellic acid promote a bigger germination of the araticum seeds. There is a difference between the accesses of the species, necessary to evaluate before being collected, and in the present study the accesses A3 is promising for harvest.